(untitled) (Journal of Hama University, 2021)
This study has investigated Clostridium perfringens infection for birds suffering from necrotic enteritis as well as healthy birds through isolating and identifying Clostridium perfringens beside discovering the existence of alpha toxin gene in isolates and studying the disease field condition. The results showed that Clostridium perfringens are existing in %17.47 of the samples. The PCR results showed the existence of alpha toxin gene in all the isolates that were collected from both infected and healthy birds. Male birds are more exposed to infection when compared to female ones as of necrotic enteritis. Having no specific studies on Clostridium perfringens on birds in Syria requires more dedicated researches in next future in order to minimize the economic losses in poultry industry.